A model of co-creation: strengthening primary health care (PHC) in Ghana through an innovative “Nyansapo” partnership - Princess Ruhama Acheampong; Kulamakan Kulasegaram; Kofi Akohene Mensah; Marie-Therese Ndiaye; Wilberforce Owusu-Ansah; Ellis Owusu-Dabo; Joseph Owusu; Jamie Rodas; Katherine Rouleau; Jennifer Wilson; Olivia Wilson (Frontiers in Medicine)
The Africa Health Collaborative (AHC) initiative embarked on a transformative ten-year collaboration with Kwame Nkrumah University of Science and Technology (KNUST) and the University of Toronto (U of T) to co-create continuing education programs geared toward augmenting the proficiency of primary care practitioners in Ghana. While upholding core principles within the AHC framework, emphasizing respect, inclusivity, equity, reciprocity, ethics, dynamism, and stewardship, seven teams of U of T and KNUST faculty engaged in collaborative efforts to design, administer, and evaluate five in-person “short courses” in Ghana on Palliative Care, Quality Improvement for Health Professionals, Prehospital Emergency Care, Community Emergency Care, and Emergency Preparedness and Response to Epidemic-Prone Diseases to approximately 100 Ghanaian primary care professionals. This paper describes a model of co-creation, highlights lessons learned from a robust evaluation process, and proposes that this co-creation model can strengthen primary health care in Ghana and ultimately transform health systems in Africa.